India's trade corridors: A shopping time model analysis for IMEEC and INSTC - Bastanifar, Iman; Khan, Kashif Hasan; Shah, Huda; Koch, Halil (Asian Economic and Financial Review, 2024)
This study evaluates India's trade potential and financial efficiency within two key corridors: the India-Middle East-Europe Economic Corridor (IMEEC) and the International North-South Transport Corridor (INSTC). This study concentrates on maximizing transaction time savings through the holding of additional real money balances, taking into account the influence of distance. An adjusted shopping time model, incorporating distances and service areas, is used. Dynamic programming calculates optimal transaction times for India's trade with members of both IMEEC and INSTC. The opportunity costs of holding money (OC) are introduced as a welfare criterion to compare the trade benefits. The study finds that distance significantly influences the optimal quantity of money for trade. India benefits more from trade with IMEEC members like the UAE, Italy, and France, and INSTC members such as Russia and Kazakhstan. IMEEC offers greater trade payoffs for India compared to INSTC, making it a more strategic option for enhancing India's global trade position. The research provides valuable insights for policymakers in optimizing trade routes and financial strategies, leveraging India’s involvement in both IMEEC and INSTC for economic gain.